Errors in Diagnosing Infectious Diseases: A Physician Survey - Haddad, Mahboubeh; Sheybani, Fereshte; Naderi, HamidReza; Sasan, Mohammad Saeed; Najaf Najafi, Mona; Sedighi, Malihe; Seddigh, Atena (Frontiers in Medicine, 2021)
Background: Infectious diseases are commonly missed or misdiagnosed. Errors in diagnosing infectious diseases not only affect the patient but also the community health. Objectives: To describe our investigation on the most common errors in diagnosing infectious diseases and their causes according to the physicians' reports. Methods: Between August 2018 and February 2019, specialist physicians and residents across Mashhad, Iran were invited to participate in a survey to report errors they had made or witnessed regarding the diagnosis of infectious diseases. Results: Overall, 465 cases were reported by 315 participants. The most common infectious diseases affected by diagnostic errors were upper respiratory tract infections (URTIs) (n = 69, 14.8%), tuberculosis (TB) (n = 66, 14.1%), pleuro-pulmonary infections (n = 54, 11.6%), central nervous system (CNS) infections (n = 51, 10.9%), and urinary tract infections (n = 45, 9.6%). Errors occurred most frequently in generating a diagnostic hypothesis (n = 259, 55/7%), followed by history taking (n = 200, 43%), and physical examination (n = 191, 41/1%). Errors related to the diagnosis of TB (odds ratio [OR]: 2.4, 95% confidence interval [CI]:0.9–5.7; P value: 0.047) and intra-abdominal infections (OR: 7.2, 95% CI: 0.9–53.8; P value: 0.02) were associated with more-serious outcomes. Conclusion: A substantial proportion of errors in diagnosing infectious diseases moderately or seriously affect patients' outcomes. URTIs, TB, and pleuropulmonary infections were the most frequently reported infectious diseases involved in diagnostic error while errors related to the diagnosis of TB and intraabdominal infections were more frequently associated with poor outcomes. Therefore, contagious and potentially life-threatening infectious diseases should always be considered in the differential diagnosis of patients who present with compatible clinical syndromes.